La infografía en el Diario La Hora y su relación en el tratamiento de la noticia en el Cantón Buena Fe - Pogo Valencia, Thalia Mishell (2019)
The infographic is an ally of the information a journalistic style has a great use in the media, technology is one of its best allies in the capture of images drawings or diagrams that capture the reader's attention the new digital era demands that the Written journals are at the forefront obtaining the advantages that the style of the infographic offers the objective is to provide reliable information and according to what is presented through the printed images. The infographic is an art to communicate the news events of the journalist to be contained, so it must be treated with respect, adhering to the norms of law and journalistic ethics does not justify altering the information with the aim of selling more because its responsibility as a means of communication It is to inform first of all with the truth. The infographic is a resource within the reach of the media, which can be used to make the article or section more interesting depending on where any subject is published and graphically explain, whatever the year of study. These are large graphic documents, which serve to present a topic to be treated, which will be accompanied by graphics, images and drawings and in some web formats, including audios and videos that make the information attractive and understandable. In fact, the elaboration of this type of material also contributes to the process of constructing the learning in a collaborative way and at the higher levels it constitutes an effective way of presenting a subject of any kind, the infographics allow to transmit the information quickly and clearly. central ideas of a topic and the retention of information by the student.